A cultura da catástrofe ambiental - Menezes, Andrea Maria Sarmento (2018)
This research has as object of study the culture of environmental catastrophe. This is the analysis of the effects that disaster movies have on people, considering the social interactions between spectators of film narratives of environmental catastrophes, about fear and insecurity about the possibility of planetary extinction (partial or total). The research approach is based on social constructionism. The method of the research adopted was the relational of the descriptive-interpretative type. Eighty-one individuals aged between six and sixty-five years of different schooling and sex participated in this study. The group device is used, focusing on the emotions and feelings manifested in the film experiences with the disaster films (1992- 2015). The main instruments of data collection were informal conversations, field diary, direct observation and audio recording of interactions among participants. The film experience, in the reception and audience of catastrophic films, produces specific effects on the conduct of the participants. Five effects are highlighted: (a) generates emotional reaction; (b) produces conscious awareness; (c) elicits unilateral direct communication through physical contact; (d) produces empathic disposition; (e) generates, produces and elicits symbolic content. However, it was observed that not all the participants demonstrated typical reactions to the phenomenon of referential-emotive micronarration, namely, fright reaction, followed by speech acts, direct reflex physical contact with other participants and laughing reaction. It was noticed that the different reactions to the products of the film industry, in the case of catastrophes, explain the particularity and the singularity of practical social life, thus avoiding the universalist approach in which social actors do not reflect on what they do, when they do. On the other hand, the symbolic dimensions of cognition, when not properly situated in the course of the debate on the filmic experience, produce a reduction effect of the mental operations, elaborated by the agents themselves with respect to the disaster films. The circulation (or explicit indication) among research participants of the need for comment on two different discursive plans was perceived: (a) reactive plans (of sensory-perceptive sensitivity) aimed at activation and saturation, in which emotion and the feeling predominates; (b) action plans (active base) focused on the decision to engage and participate directly or indirectly in the search for involvement with issues pertaining to nature, man and the possibilities of extinction of life on the planet. We conclude that the fear and insecurity of planetary extinction (partial or total), conveyed by the disaster films brings to the center of the debate the emotions and the feelings as an in separate part of the environmental issues and the variety of behaviors observed in contemporary social practices.